Efficiency Analysis of Aquifer Parameters of Different Wells in Khabat Basin - Pola O. Abdalrahman; Dana K. Mawlood (Zanco Journal of Pure and Applied Sciences, 2023)
The study presented in this paper is the efficiency analysis of aquifer parameters in Khabat Basin through data collected from pumping test of the wells. The important indicator of the wells yield can be evaluated as the well efficient or not. Wells is considered as an efficient well if the efficiency is more than 70%. The pumping test is conducted to estimate the aquifer parameters (transmissivity and storativity) using (AQTESOLV4.5) software. Modified cooper Jacob (1946) for single pumping well is provides for estimation aquifer parameters. The results showed that the value of transmissivity is within the standard range for unconfined aquifer, while storativity is overestimated this was due to the total head losses in the pumping the well. Also, the objective of this study using aquifer response to pumping test to calculate the cone of depression than finding out the storativity of the aquifer.